Práticas de leitura e de escrita de alunos surdos na escola regular: das posições-sujeito a seus efeitos discursivos - Gondim, Onilda Aparecida (2020)
This thesis turns its attention to the theme of inclusive education, considering the reality of two public schools of basic education in the state of Goiás, Brazil. More precisely, our interest fell on the way in which reading and writing practices in Portuguese took place for deaf students enrolled in these schools. Given the specificity of inclusive education, we followed both the classes that took place in the regular teaching classroom and those that took place in the Specialized Educational Service (AEE). As a guideline for theoretical and methodological procedures, we worked with the following general objective: to problematize the way in which deaf students are signified in and by reading and writing practices in inclusive schools. In such a process, we had in mind the relationship students kept with Libras and Portuguese. Other processes of meaning, for instance, iconicization and typing, among others, were also considered. In relation to our specific objectives, we outlined the following: to identify the pre-constructed issues that ended up anchoring the didactic-pedagogical relationship among teachers, deaf students and interpreters; to analyze the processes of signification (“syntagmatization”, “signaling”, “typing”, “iconization”, among others) that constitute the classroom discursive game. This allowed us to map the positions taken by participants and their effects for the reading and writing practices in the Portuguese class; to analyze how deaf students become meaning-makers in their process of learning how to read and write in Portuguese. Taking into account that the relationship between different processes of meaning making gain materialization in the discursive game of classroom, the research question we formulated was how reading and writing practices were configured in the regular classroom and in the AEE for deaf students. In order to answer such a question, we hypothesized that although there are official discursivities that signify the relationship of deaf students, assuming that they are automatically identified with reading and writing practices in Portuguese, the lack of inscription in Libras ends up engendering the prevalence of empirical and formal repetition practices of these students with reading and writing activities. Thus, the specific mode of memory functioning, in the discursive game of the classes followed, provokes a historical repetition of meanings. Theoretically, we joined the Discourse Analysis studies based on the theorizations of Pêcheux (1969, 1975, 1983), Courtine (1981), Orlandi (1984, 1987, 1998, 2007, 2009, 2016, 2020), Grigoleto (2005) and Indursky (2011). Our research corpus was constructed by observing and recording in video classes in the regular classroom for five months and, also, in the AEE For a period of three months. The analyzes showed evidences that the reading and writing practices developed by teachers and interpreters did not revert in favor of students. As a consequence, they were not able to constitute themselves in discursive processes relevant to the relationship between Portuguese and Libras. Other processes of signification ended up rarefying this other possible relationship between Portuguese and Libras. Thus, in most of the analyzed classes, the practices of reading (oral interpretation) and writing were meant to reinforce empirical repetition. As a consequence, meaning was not historicized in the classroom. Keywords: Inclusion; deafness, reading, writing, discursivity.